Meta-analysis on extraction methods, pharmacological activities, and cultivation techniques of Curcuma xanthorrhiza Roxb. - Rahmadansah Rahmadansah; Dyah Sulistyani Rahayu; Fadila Raisyadikara; Bambang Pontjo Priosoeryanto; Waras Nurcholis (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2023)
Javanese turmeric (Curcuma xanthorrhiza Roxb.) is important for study due to its increasing economic value in many aspects including marker-associated compounds for curcuminoids and xanthorrhizol. This systematic review aimed to summarize and find information about C. xanthorrhiza starting from its pharmacological activity and mechanism as an anticancer, anti-inflammatory, and antioxidant extraction process, and cultivation techniques. The data were obtained from relevant journals in national and international scientific databases PubMed, Scopus, Google Scholar, Web of Science, SINTA, ScienceDirect, and Wiley Online from 2000 to 2023. Results showed that from the perspective of anti-inflammatory pharmacological activities, xanthorrhizol inhibits pain response and inflammatory response. Its antioxidant activity showed a contribution to inhibiting oxidation which also successfully inhibits cancer cell proliferation. The extraction method of xanthorrhizol and curcuminoid compounds with Ultrasonic-Assisted Extraction (UAE) 20-2000 kHz performs better than other methods. C. xanthorrhiza cultivation techniques under shading produce better rhizomes. Based on research on cultivation techniques, extraction methods, and pharmacological activities, C. xanthorrhiza has an important role in the future.